PENERAPAN METODE PENEMUAN TERBIMBING DALAM MENINGKATKAN KEMAMPUAN BERPIKIR LOGIS ANAK USIA 3-4 TAHUN DI PPT TERATAI KENJERAN SURABAYA - Sri Karmiati (Universitas Narotama, 2020)
Abstract This study aims to determine the increase in the ability to think logically children aged 3-4 years in PPT Kenjeran Surabaya through the application of the Guided Discovery Method. This type of research is classroom action research with subjects of 15 children aged 3-4 years and the object is the application of guided discovery methods in improving logical thinking skills. Data collection using the method of observation, interviews and documentation. The data collected is analyzed and reflected descriptively quantitatively. The results showed that in the first cycle of action as many as 4 children (25%) the ability of logical thinking children develop very well (BSB) this shows that the level of children's logical thinking ability is still low. Actions in cycle II have an increase in the ability to think logically by 13 children (80%) with very well developed criteria (BSB). So it can be concluded that the application of the Guided Discovery Method in improving the logical thinking ability of children aged 3-4 years in PPT Lotus Surabaya can be applied with good results. Key words: Guided Discovery Method, logical thinking